Development of REACT-Oriented Student Worksheets to Improve Physics Learning Outcomes - Helmi Abdullah; Bunga Dara Amin; Awaliyah Salam (Postgraduate, University of Mataram, 2023)
This research is a developer research that aims to develop student worksheets. The subjects of this research trial were 35 students of class XI MIPA 2 of State Senior High School 1 Majene. This study uses the ADDIE model development. The instruments used in this study were validation sheets for student worksheets, teacher response questionnaires and student responses, as well as physics learning outcomes test instruments. The eligibility criteria for student worksheets are seen from the validation aspect. The practicality criteria can be seen from the assessment of the teacher's and students' responses to the students' worksheets, and the effectiveness criteria can be seen from the increase in physics learning test results. Based on the results of the analysis, it can be concluded that: (1) Student worksheets developed based on expert judgment using Aiken V index analysis are declared valid and suitable for use with minor revisions; (2) Student worksheets in terms of the physics teacher's response are in the very good category; (3) Student worksheets in terms of student responses are in the very good category; (4) The application of student worksheets seen from the ability of physics learning outcomes analyzed by N-gain obtained an average value of 0.7 in the high category which means that there is an increase in the ability of physics learning outcomes so that it can be said that student worksheets which was developed is effective in improving physics learning outcomes in Majene 1 State Senior High School